LEMBAGA PAUD DI LINGKUNGAN PERUMAHAN UNTUK PENYEBARAN AKSES DAN PENINGKATAN KUALITAS PENDIDIKAN - Subijanto, Subijanto (JIV-Jurnal Ilmiah Visi, 2016)
The existence of Early Childhood Education (ECE) has become a need for equalizing the access to educational service for early age children (0-6 years old). This also became the policy of Ministry of Education and Culture up to 2014. However, the policy could not be implemented completely and equally, particularly in the housing compound in urban and rural areas. The purpose of this policy study is to review the improvement of service accessibility and ECE quality. This study applied document study on legal products and relevant document related to ECE. The result of the study indicates (1) The distribution of ECE in the housing compound is unequal, (2) ECE services are badly needed by the community in the housing compound, (3) improvement access to ECE services in the housing compound provides educational opportunity to all early aged children with different economic and social status background of their parents, and (4) instruction based on integrative holistic approach can improve the access and service quality of ECE. It can be concluded, the access to ECE is not well distributed and expanded yet and not well supported by developer and local government.